A Gradient pH‐Sensitive Polymer‐Based Antiviral Strategy via Viroporin‐Induced Membrane Acidification (Adv. Mater. 18/2022). Issue 18 (5th May 2022) - Sun, Yizhe; Gong, Lidong; Yin, Yue; Zhang, Lei; Sun, Qiangming; Feng, Kai; Cui, Yimin; Zhang, Qiang; Zhang, Xuehui; Deng, Xuliang; You, Fuping; Lu, Dan; et al.
Abstract : Antiviral Strategies A gradient pH‐sensitive (GPS) polymer is developed by Fuping You, Dan Lu, Zhiqiang Lin, and co‐workers in article number 2109580 . In response to an acidified membrane, the GPS polymer with dye conjugation illuminates, targets, and lyses the envelope of viruses, resulting in leakage of viral nucleic acid and a broad‐spectrum activity of the GPS polymer against a variety of viruses.